An efficient hybrid method for fast phased array pattern synthesizing. Issue 12 (12th September 2022) - Zhou, Zicheng; Lu, Xiaopeng; Huang, Guan‐Long; Gu, Changqing
Abstract: A novel and fast array synthesis method simultaneously combining the advantages of genetic algorithm (GA), alternating projection method (APM), and differential evolution (DE) is proposed in this work. The APM adopts fast Fourier transform (FFT), and the far‐field calculation is mathematically simplified to multiplication with a common matrix, which could be faster than inverted‐FFT (IFFT) for thousands of individuals of the same small array. Then an effective fitness evaluating method with multi‐objective is developed, which could be adjusted according to specific needs such as array side lobe suppression, beam‐broaden, and beam‐shaping. To demonstrate the feasibility of the proposed method, several array synthesis examples are presented and the results show that the proposed method has good robustness, convergence, and global searching ability.